Alpha-Synuclein Glycation and the Action of Anti-Diabetic Agents in Parkinson's Disease - König, Annekatrin (2022)
Parkinson's disease (PD) is a neurodegenerative disorder with complex etiology and variable pathology. While a subset of cases is associated with single-gene mutations, the majority originates from a combination of factors we do not fully understand. Thus, understanding the underlying causes of PD is indispensable for the development of novel therapeutics. Glycation, the non-enzymatic reaction between reactive dicarbonyls and amino groups, gives rise to a variety of different reaction products known as advanced glycation end products (AGEs). AGEs accumulate over a proteins life-time, and increased levels of glycation reaction products play a role in diabetic complications. It is now also becoming evident that PD patients also display perturbed sugar metabolism and protein glycation, including that of alpha-synuclein, a key player in PD. Here, we hypothesize that anti-diabetic drugs targeting the levels of glycation precursors, or promoting the clearance of glycated proteins may also prove beneficial for PD patients.